2019
DOI: 10.31665/jfb.2019.6182
|View full text |Cite
|
Sign up to set email alerts
|

Guarana as a source of bioactive compounds

Abstract: A high daily intake of fruits and vegetables is an important strategy to promote health. The mechanism explaining the health benefits of plant food materials is attributed, at least in part, to their high content of bioactive phenolics. Guarana (Paullinia cupana) is a typical product from Amazon biota and, mainly as a source of caffeine; its seeds are commonly used as stimulants. However, guarana seeds are also rich in catechin, epicatechin, procyanidin B1, and procyanidin B2. Guarana exhibits potential health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, guarana possesses many other bioactive compounds, including PACs, that exhibit in vitro and in vivo health-promoting effects. In fact, their potential anticancer, antioxidant, antihyperglycemic and anti-obesity effects have recently been reported (da Silva et al, 2019).…”
Section: Proanthocyanidins (Pacs)mentioning
confidence: 99%
“…However, guarana possesses many other bioactive compounds, including PACs, that exhibit in vitro and in vivo health-promoting effects. In fact, their potential anticancer, antioxidant, antihyperglycemic and anti-obesity effects have recently been reported (da Silva et al, 2019).…”
Section: Proanthocyanidins (Pacs)mentioning
confidence: 99%
“…The Brazilian Food Supplement Law recently recognized that guarana contains bioactive substances, hence supporting its role as a functional food ingredient [28]. Both animal and human studies have found that the consumption of guarana powder was safe and caused no toxicity in small doses (30 mg/kg for animals and 200 mg/day for humans) [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Syringic acid that was identified in this work is also found in nuts, fruits, culinary herbs, and their processing by-products (Alvarez-Parrilla et al, 2018;Mirfat et al, 2018;Senanayake, 2018;Shahidi and Hossain, 2018). In contrast, while several feedstocks show catechin in their phenolic profile (Amarowicz and Shahidi, 2018;Silva et al, 2018;Silva et al, 2019), the presence of gallocatechin is not as common.…”
Section: Total Phenolics and Maldi-tof-ms Analysismentioning
confidence: 53%